Integration of Human Factors for Assembly Systems of the Future - Roesmann, Daniel; Gräßler, Iris (The Digital Twin of Humans)

Conceptions and Feasibility Study of Fiber Orientation in the Melt as Part of a Completely Circular Recycling Concept for Fiber-Reinforced Thermoplastics - Moritzer, Elmar; Tölle, Lisa; Greb, C.; Haag, M. (Journal of Composites Science)

Polypropylene Degradation on Co-Rotating Twin-Screw Extruders - Schöppner, Volker; Altepeter, Matthias; Austermeier, Laura; Wanke, Sven; Meinheit, Philipp (Polymers 2023)

Investigation of the Homogenization Performance of Various Faceted Mixers and Optimization with Regard to Mixing as well as Pressure Throughput Behavior - Schöppner, Volker; Frank, Maximilian

Design of a test bench for measuring the degradation behavior of plastics during processing - Schall, Christoph Wilhelm Theodor; Schöppner, Volker (PPS36)
Keywords: Computing Resources Provided by the Paderborn Center for Parallel Computing

Material Characterization of Polypropylene and Polystyrene Regarding Molecular Degradation Behavior - Schöppner, Volker; Schall, Christoph Wilhelm Theodor (Materials)

Characterization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian (Welding in the World)

POTENTIALS AND GOALS OF MODELS IN STRATEGIC PRODUCT PLANNING AND INNOVATION MANAGEMENT - Gräßler, Iris; Koch, Anna-Sophie; Tusek, Alena Marie (Proceedings of the Design Society)
Abstract New trends and technologies in product creation increase complexity, but at the same time create new potentials such as efficiency rise in task processing by Artificial Intelligence. Established models in the early phase of product creation such as the W-model or the Aachener Innovation Management model, do not fully exploit these new potentials in the field of strategic product planning and innovation management (SPPIM). For this reason, existing models are analysed in SPPIM in order to derive a requirements profile consisting of potentials and goals for a new model. A new model in SPPIM lays the foundation to support companies in enabling a more efficient task fulfilment by taking advantage of new technologies and trends. To guide the development of advanced SPPIM models, the derived potentials and goals are applied to the guideline VDI 2220:1980.

Interdependency study of design guidelines - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)

Sustainable product life cycle - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)

Begriffe der strategischen Produktplanung und -entwicklung. Produkt und hybride Leistung - Gräßler, Iris; Ovtcharova, Jivka; Dattner, Michael; Dietert, Tilko; Dietz, Patrick; Elstermann, Matthes; Fayet, Celestin; Hauck, Andreas; Häuser, Frank; Fischer, Holger; Herzog, Michael; Köhler, Christian; et al.

Post-pandemic online mathematics and statistics support: Practitioners’ opinions in Germany and Great Britain & Ireland - Gilbert, H.; Schürmann, M.; Liebendörfer, M.; Lawson, D.; Hodds, M. (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Fachdidaktisches Design von Begründungsvideos im Projekt studiVEMINTvideos - Biehler, Rolf; Guntermann, Dominik; Liebendörfer, Michael; Krämer, Sandra; Schlüter, Sarah (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Erfassung und Vergleich (mathematischer) Eingangsvoraussetzungen angehender Studierender verschiedener mathematikhaltiger Studiengänge - Göller, Robin; Gildehaus, Lara; Liebendörfer, Michael; Besser, Michael (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2021. Beiträge zum gleichnamigen Online-Symposium am 12 November 2021 aus Bochum)

Zu digital - zu viel - zu schwer? Qualitative Einsichten in das Erleben und Handeln von Erstsemester-Studierenden der Mathematik während der Corona-Pandemie - Kempen, Leander; Liebendörfer, Michael (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2021. Beiträge zum gleichnamigen Online-Symposium am 12 November 2021 aus Bochum)

Bearbeitungsmuster von Studierenden im Umgang mit formalen Definitionen im Kontext konstanter Folgen - Schlüter, Sarah; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Förderung prozeduraler Flexibilität durch Lernvideos mit interaktiven Aufgaben - Krämer, Sandra; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Preservice teachers’ mathematics-related values and expectancy in the transition from school to university
Many preservice mathematics teachers lose their motivation during their first year at university. This phenomenon has been repeatedly described in recent years but is not yet fully understood. Since motivation may relate to different objects such as mathematics or teaching, we aim to qualitatively reconstruct different facets of the central motivational constructs of Situated-Expectancy-Value theory (intrinsic value, attainment value, utility value, cost, and expectancy of success) for preservice mathematics teachers. The analysis of longitudinal group interviews of 14 preservice higher-secondary mathematic teachers from a German university revealed different objects of motivation (e.g., teaching mathematics, scientific mathematics, procedural mathematics, or proof-based mathematics) in preservice teachers' values and expectancy of success. Furthermore, relations between those values and expectancy of success were identified that played a significant role in preservice teachers’ motivational development over their first semester (e.g., relations of attainment value for scientific mathematics and psychological cost). Theoretical and practical implications towards a teaching-specific conceptualization of expectancy of success and values and value interventions are being discussed.

Determination of Correlations between Melt Quality and the Screw Performance Index in the Extrusion Process - Trienens, Dorte; Schöppner, Volker; Bunse, Robin (Polymers 2023)

Improvement of a method for the correction of wall slip effects within the rheological measurements of filled rubber compounds - Schöppner, Volker; Kleinschmidt, Dennis (SPE Polymers)